DETERMINATION OF OPERATING PARAMETERS OF DRYING EQUIPMENT OF A WALNUT PROCESSING LINE - TSURKAN, OLEH; SPIRIN, ANATOLII; RUTKEVYCH, VOLODYMYR; DIDYK, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The results of applied scientific research on the development and justification of the design and technological parameters of a convective-vibration dryer for post-harvest processing of walnuts are presented. The insufficient study of the mutual influence of thermal, aerodynamic and vibration factors on the energy efficiency of the walnut drying process necessitates the need for comprehensive research and the development of appropriate analytical models. This will allow determining rational design and technological parameters of the drying equipment and forming scientifically based criteria for improving technological lines for processing walnut raw materials. The main problems of traditional drying methods are identified, in particular, uneven heating, loss of biologically active substances and high specific energy consumption. A technical solution is proposed that combines controlled convective supply of the coolant and mechanical vibration to intensify mass and heat transfer. Based on experimental studies, the main design and technological parameters of the drying equipment were determined. These include: coolant temperature, its supply intensity, drying duration, product layer thickness and air circulation parameters depending on the initial moisture content of nuts. Additionally, the dependence of specific energy consumption on changes in equipment operating modes was analyzed, which allowed forming criteria for energy efficiency of the technological process.Based on multifactor mathematical modeling, rational drying operating parameters are determined based on the criterion of minimizing specific energy consumption. The results of the study confirm the feasibility of using an integrated approach to optimizing the drying process of nut raw materials and indicate an increase in the energy efficiency of technological equipment.